A method for preparing a flexing-resistant rubber composition for a new energy vehicle tire
Patent Information
- Application Number
- CN202611272580.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-21
- Publication Date
- 2026-09-18
AI Technical Summary
但该方案主要围绕胎侧橡胶的耐老化和不变色性能进行改进,其填料体系中白炭黑、TiO2等仍主要以常规组分形式加入,并未针对白炭黑和TiO2在橡胶基体中的分散性进行预先设计,也难以降低界面老化对裂纹产生和扩展的影响,限制了轮胎橡胶耐屈挠性能的提升
本发明以天然橡胶NR和乳聚丁苯橡胶ESBR作为橡胶基材,并配合二次颗粒、改性二氧化钛粉和炭黑N339等材料制备汽车轮胎用耐屈挠橡胶组合物。其中,天然橡胶NR具有较好的弹性恢复和抗撕裂能力,乳聚丁苯橡胶ESBR具有较好的耐磨性和形变支撑能力,二者并用可在弹性恢复、耐磨支撑和裂纹抑制方面形成互补。通过分阶段混炼,使二次颗粒、改性二氧化钛粉和炭黑N339逐步分散于橡胶基体中,并通过硅烷偶联剂Si69提高材料之间的界面结合能力,从而形成较均匀的补强网络,减少局部应力集中,延缓微裂纹萌生和扩展,提高橡胶组合物的耐屈挠性能和耐老化性能。
Smart Images

Figure CN122772282A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of tire rubber materials technology, and specifically to a method for preparing a flexurally resistant rubber composition for new energy vehicle tires. Background Technology
[0002] Tire rubber compositions typically need to strike a balance between elasticity, strength, abrasion resistance, and flexural strength. For tires of new energy vehicles, the dynamic deformation experienced during starting, stopping, steering, and high-speed rolling is more frequent, thus placing higher demands on the flexural strength of the rubber composition.
[0003] Tire rubber compositions typically employ a blend of natural rubber, styrene-butadiene rubber, carbon black, silica, silane coupling agents, and vulcanization systems to enhance the overall performance of the compound. While silica offers good reinforcing properties, its dispersion within the rubber matrix directly impacts both the reinforcing effect and fatigue resistance. Furthermore, tires are exposed to ultraviolet radiation during use, which can cause the rubber molecular chains to age and break, making cracks more likely to form and propagate. Therefore, relying solely on conventional silica, carbon black, and ordinary antioxidant systems is insufficient to meet the flexural strength requirements of automotive tires.
[0004] Patent application CN113416353A discloses an aging-resistant and colorfast sidewall rubber composition and its preparation method. This method introduces an organic porous silica-loaded antioxidant, grafting the antioxidant onto the surface of porous silica particles to reduce antioxidant migration and ejection, thereby improving the rubber's aging resistance and other properties. However, this approach primarily focuses on improving the aging resistance and colorfastness of the sidewall rubber. The filler system, including silica and TiO2, is mainly added in conventional forms without pre-designing for the dispersion of silica and TiO2 in the rubber matrix. This also makes it difficult to reduce the impact of interfacial aging on crack initiation and propagation, thus limiting the improvement of the tire rubber's flexural strength.
[0005] In summary, there is a need to provide a method for preparing a flexurally resistant rubber composition for new energy vehicle tires to solve the problems existing in the prior art. Summary of the Invention
[0006] In view of this, the present invention provides a method for preparing a flexurally resistant rubber composition for new energy vehicle tires, so as to improve the flexural resistance and aging resistance of tire rubber.
[0007] To achieve the above objectives, a method for preparing a flexurally resistant rubber composition for new energy vehicle tires includes the following preparation steps:
[0008] S1. Mix 10-12 parts of natural rubber NR and 88-90 parts of emulsion styrene-butadiene rubber ESBR for initial plasticizing, then add 50-56 parts of secondary granules, 4-5 parts of modified titanium dioxide powder, zinc oxide, stearic acid, protective wax, antioxidant RD, environmentally friendly aromatic oil TDAE, C9 petroleum resin and accelerator DPG for compounding; then add silane coupling agent Si69 and continue compounding, sheet and cool to obtain a first stage of masterbatch; S2. Mix the first stage masterbatch, carbon black N339 and antioxidant 4020, heat to 130~145℃ for secondary mixing, and then sheet and cool to obtain the second stage masterbatch. S3. Mix the second-stage masterbatch, sulfur, accelerator CZ and anti-scorching agent CTP, heat and finish the process, pass through a thin sheet, and cool to obtain a flexural rubber composition. The modified titanium dioxide powder was prepared by dispersing titanium dioxide powder in an aqueous ethanol solution, adjusting the pH of the system to acidic, adding γ-aminopropyltriethoxysilane, refluxing, drying, dispersing in anhydrous ethanol, adding N,N'-dicyclohexylcarbodiimide and 3,5-di-tert-butyl-4-hydroxyphenylacetic acid to continue the reaction, and then filtering, washing and drying. The secondary particles were obtained by spray drying after attapulgite clay and silica were bridged with silane coupling agent Si69.
[0009] This invention uses natural rubber (NR) and emulsion styrene-butadiene rubber (ESBR) as rubber base materials, and combines them with secondary particles, modified titanium dioxide powder, carbon black N339, an anti-aging protection system, and a vulcanization system to prepare a flexurally resistant rubber composition for automotive tires. Natural rubber (NR) possesses good elastic recovery and tear resistance, improving the toughness of the rubber compound during repeated flexing. Emulsion styrene-butadiene rubber (ESBR) has good abrasion resistance and deformation support, which helps ensure the overall mechanical properties of the rubber compound. By using natural rubber (NR) and emulsion styrene-butadiene rubber (ESBR) in combination, the rubber base materials complement each other in terms of elastic recovery, abrasion resistance, and crack suppression. Simultaneously, a staged mixing method is used to gradually disperse the secondary particles, modified titanium dioxide powder, and carbon black into the rubber matrix, and the interfacial bonding ability between materials is improved through the use of silane coupling agent Si69, thereby forming a more uniform reinforcing network, reducing local stress concentration, delaying the initiation and propagation of microcracks, and improving the flexural and aging resistance of the rubber composition.
[0010] The modified titanium dioxide powder prepared in this invention serves as a functional filler to improve the flexural strength of rubber compositions used in automotive tires. This invention uses titanium dioxide powder as a matrix. First, it grafts the powder onto the surface using the silane coupling agent γ-aminopropyltriethoxysilane. The silanol groups generated from the hydrolysis of γ-aminopropyltriethoxysilane undergo a condensation reaction with the titanium hydroxyl groups on the surface of the titanium dioxide powder, forming an organic coupling layer on the surface of the titanium dioxide powder. This improves its compatibility with natural rubber and latex styrene-butadiene rubber matrices, thereby improving the dispersibility of the titanium dioxide powder in the rubber matrix. Then, using N,N'-dicyclohexylcarbodiimide as a condensing agent, 3,5-di-tert-butyl-4-hydroxyphenylacetic acid reacts with γ-aminopropyltriethoxysilane, anchoring the phenolic antioxidant groups of 3,5-di-tert-butyl-4-hydroxyphenylacetic acid to the surface of the titanium dioxide powder. This reduces the possibility of migration or precipitation during repeated flexing of the rubber, thus providing durable antioxidant properties and effectively slowing down the breakage of molecular chains during thermo-oxidative aging. In addition, the ultraviolet light shielding function of titanium dioxide and the antioxidant effect of phenolic antioxidant groups form a synergistic effect, which can reduce the generation of microcracks under the combined action of thermo-oxidative aging and flexural stress, and improve the flexural resistance of rubber compositions for automobile tires.
[0011] Optionally, the secondary particles are prepared by dispersing attapulgite clay in deionized water, adding silica and stirring, adjusting the pH to 5-6 to obtain a composite solution; adding silane coupling agent Si69 to an ethanol aqueous solution, adjusting the pH to 5-6 and stirring evenly, then pouring it into the composite solution, heating and stirring to react, and finally spray drying, cooling and sieving.
[0012] This invention utilizes the silane coupling agent Si69 to chemically bridge fillers such as attapulgite clay and silica. After spray drying, secondary particles are obtained, which improve the flexural strength of the rubber composition. The silanol groups generated by the hydrolysis of the silane coupling agent Si69 can undergo condensation reactions with the silanol groups of silica and attapulgite clay, respectively, forming a silane bridging effect between the silica particles and the rod-shaped structure of the attapulgite clay. Simultaneously, the organic segments in the Si69 molecule reduce the surface polarity of the filler, improving the compatibility between the secondary particles and the rubber matrix, thereby resulting in higher uniform dispersion of the secondary particles within the rubber matrix. Furthermore, when the rubber material is subjected to repeated flexural forces, the silica particles bear the compressive load and transfer the stress to the attapulgite clay. The attapulgite clay, with its high aspect ratio structure, transfers the stress along its length, playing a role in blocking and deflecting cracks during the microcrack propagation process, thus extending the crack propagation path and delaying the propagation of microcracks, thereby further improving the flexural resistance of the rubber composition for automobile tires.
[0013] In this invention, secondary particles are prepared by bridging silica and attapulgite clay using the silane coupling agent Si69. The slender rod-like structure of attapulgite clay can provide support, block, and deflect cracks during repeated flexing of the rubber composition. Combined with the reinforcing effect of silica, this extends the microcrack propagation path, reduces local stress concentration, and thus improves the flexural resistance of the rubber composition.
[0014] Optionally, the modified titanium dioxide powder is prepared by mixing titanium dioxide powder and an aqueous ethanol solution, ultrasonically dispersing for 35-45 min, heating to 70-75℃, adjusting the pH to 5-6 with glacial acetic acid, adding γ-aminopropyltriethoxysilane, refluxing for 4-4.5 h, drying, dispersing in anhydrous ethanol, heating to 95-97℃, adding N,N'-dicyclohexylcarbodiimide and 3,5-di-tert-butyl-4-hydroxyphenylacetic acid, reacting for 3-4 h, filtering, washing 2-3 times with anhydrous ethanol, and vacuum drying at 90-95℃ for 10-12 h.
[0015] In this invention, γ-aminopropyltriethoxysilane can form a coupling layer on the surface of titanium dioxide powder, improving the compatibility between titanium dioxide powder and natural rubber (NR) and latex styrene-butadiene rubber (ESBR) matrix, and improving the dispersibility of titanium dioxide powder in the rubber matrix. Simultaneously, under the action of N,N'-dicyclohexylcarbodiimide, the carboxyl groups in 3,5-di-tert-butyl-4-hydroxyphenylacetic acid can undergo an amidation reaction with the amino groups introduced by γ-aminopropyltriethoxysilane, anchoring phenolic antioxidant groups to the surface of titanium dioxide powder, reducing the possibility of their migration or precipitation, thereby improving the resistance to thermo-oxidative aging and enhancing the aging resistance of the rubber composition.
[0016] Optionally, in step S1, natural rubber NR and latex styrene-butadiene rubber ESBR are mixed and heated to 50~70℃ for initial plasticizing for 8~12 minutes. Secondary granules, modified titanium dioxide powder, zinc oxide, stearic acid, protective wax, antioxidant RD, environmentally friendly aromatic oil TDAE, C9 petroleum resin and accelerator DPG are added and mixed for 3~5 minutes. When the temperature rises to 110~120℃, silane coupling agent Si69 is added and mixing continues. When the temperature rises to 145~155℃, the glue is discharged, and the sheet is cooled and allowed to stand for 16~18 hours to obtain a first stage of masterbatch.
[0017] In this invention, natural rubber (NR) and emulsion styrene-butadiene rubber (ESBR) are first mixed and pre-plasticized, which can improve the processing fluidity of the rubber matrix. This facilitates the entry of fillers such as secondary particles and modified titanium dioxide powder into the rubber matrix and achieves uniform dispersion. It can also reduce local stress concentration caused by filler agglomeration, thereby improving the uniformity and stability of the first-stage masterbatch.
[0018] Optionally, in step S2, a first-stage masterbatch, carbon black N339, and antioxidant 4020 are heated to 130~145℃ and mixed for 2~3 minutes, then sheeted and cooled to 30~40℃ to obtain a second-stage masterbatch.
[0019] Optionally, in step S3, the second-stage masterbatch, sulfur, accelerator CZ and anti-scorching agent CTP are heated to 90~110℃ and mixed for 3~5 minutes, passed through a thin sheet 3~5 times, and then sheeted and cooled for 24~26 hours to obtain a flexural rubber composition.
[0020] Optionally, the rubber composition further comprises the following raw materials in parts by weight: 3-3.5 parts zinc oxide, 2-2.2 parts stearic acid, 1.5-1.8 parts protective wax, 1-1.1 parts antioxidant RD, 8-9 parts environmentally friendly aromatic oil TDAE, 3-3.5 parts C9 petroleum resin, 0.8-1 part accelerator DPG, 3.8-4 parts silane coupling agent Si69, 14-15 parts carbon black N339, 2-2.2 parts antioxidant 4020, 1.6-1.7 parts sulfur, 1.6-1.7 parts accelerator CZ, and 0.15-0.16 parts scorching inhibitor CTP.
[0021] Optionally, the modified titanium dioxide powder comprises the following raw materials in parts by weight: 4-5 parts titanium dioxide powder, 40-50 parts 90wt% aqueous ethanol solution, 0.1-0.11 parts γ-aminopropyltriethoxysilane, 0.12-0.15 parts N,N'-dicyclohexylcarbodiimide and 0.15-0.16 parts 3,5-di-tert-butyl-4-hydroxyphenylacetic acid.
[0022] Optionally, the secondary particles comprise the following raw materials in parts by weight: 6-10 parts attapulgite clay, 45-50 parts silica, 400-500 parts deionized water, 0.8-1.5 parts silane coupling agent Si69, and 15-25 parts 70 wt% aqueous ethanol solution.
[0023] The above-described technical solution of the present invention has at least the following beneficial effects: This invention uses natural rubber (NR) and emulsion styrene-butadiene rubber (ESBR) as rubber base materials, and combines them with secondary particles, modified titanium dioxide powder, and carbon black N339 to prepare a flexurally resistant rubber composition for automotive tires. Natural rubber (NR) possesses good elastic recovery and tear resistance, while emulsion styrene-butadiene rubber (ESBR) exhibits good abrasion resistance and deformation support. The combination of these two materials complements each other in terms of elastic recovery, abrasion support, and crack suppression. Through staged mixing, the secondary particles, modified titanium dioxide powder, and carbon black N339 are gradually dispersed in the rubber matrix. The interfacial bonding ability between materials is improved through the use of silane coupling agent Si69, thereby forming a more uniform reinforcing network, reducing local stress concentration, delaying the initiation and propagation of microcracks, and improving the flexural resistance and aging resistance of the rubber composition.
[0024] The modified titanium dioxide powder prepared by this invention can improve the flexural strength of rubber compositions for automotive tires. The silanol groups generated from the hydrolysis of γ-aminopropyltriethoxysilane can undergo a condensation reaction with the titanium hydroxyl groups on the surface of titanium dioxide powder, forming an organic coupling layer on the surface of the titanium dioxide powder. This improves its compatibility with natural rubber (NR) and latex styrene-butadiene rubber (ESBR) matrices, and also improves its dispersibility. Under the action of N,N'-dicyclohexylcarbodiimide, 3,5-di-tert-butyl-4-hydroxyphenylacetic acid reacts with γ-aminopropyltriethoxysilane, anchoring phenolic antioxidant groups to the surface of the titanium dioxide powder, reducing the possibility of their migration or precipitation, thereby providing durable antioxidant properties and slowing down the breakage of rubber molecular chains during thermo-oxidative aging. Through the synergistic effect of titanium dioxide and 3,5-di-tert-butyl-4-hydroxyphenylacetic acid, the flexural strength and aging resistance of the rubber composition are improved. Attached Figure Description
[0025] Figure 1 The infrared reflectance spectrum of the flexurally resistant rubber composition for new energy vehicle tires prepared in Example 1 of this invention is shown. Detailed Implementation
[0026] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. The described embodiments are some embodiments of the present invention, and all other embodiments obtained by those skilled in the art based on the described embodiments of the present invention are within the scope of protection of the present invention.
[0027] Example 1 Five parts of titanium dioxide powder (model CY-T200, purchased from Hangzhou Jiupeng New Materials Co., Ltd.) and 50 parts of 90wt% ethanol aqueous solution were mixed and poured into a three-necked flask. The mixture was ultrasonically dispersed for 45 min, heated to 75℃ in an oil bath, and the pH was adjusted to 6 by adding glacial acetic acid. 0.11 parts of γ-aminopropyltriethoxysilane were added, and the mixture was refluxed for 4.5 h. The mixture was then placed in a drying oven and dried at 95℃ for 2 h. The resulting powder was dispersed in 50 parts of anhydrous ethanol, heated to 97℃, and 0.15 parts of N,N'-dicyclohexylcarbodiimide and 0.16 parts of 3,5-di-tert-butyl-4-hydroxyphenylacetic acid were added. The reaction was continued for 4 h, filtered, and washed three times with anhydrous ethanol. The mixture was then heated to 95℃ and vacuum dried for 12 h to obtain modified titanium dioxide powder.
[0028] Ten parts of attapulgite clay (0.15~0.5μm in length and 0.05~0.15μm in diameter, purchased from Xuyi Taihe High-tech Technology Co., Ltd.) were added to 500 parts of deionized water and stirred at 1200 rpm for 30 min. 50 parts of silica were added and stirred for another 40 min. Glacial acetic acid was added to adjust the pH to 6 to obtain a composite solution. 1.5 parts of silane coupling agent Si69 were added to 25 parts of 70wt% ethanol aqueous solution, the pH was adjusted to 6 and stirred for 60 min. The solution was poured into the composite solution and heated to 70℃ and stirred for 4 h. The resulting slurry was spray-dried with the inlet air temperature controlled at 180℃ and the outlet air temperature at 90℃. It was then vacuum-dried at 105℃ for 4 h. After cooling, it was passed through a 200-mesh sieve to obtain secondary particles.
[0029] First stage of mixing: Mix 12 parts of natural rubber NR and 90 parts of emulsion styrene-butadiene rubber ESBR, heat to 70℃, and stir at 70 rpm for 12 minutes for initial plasticization; add 56 parts of secondary granules, 5 parts of modified titanium dioxide powder, 3.5 parts of zinc oxide, 2.2 parts of stearic acid, 1.8 parts of protective wax, 1.1 parts of antioxidant RD, 9 parts of environmentally friendly aromatic oil TDAE, 3.5 parts of C9 petroleum resin and 1 part of accelerator DPG in sequence, and continue mixing for 5 minutes; when the rubber compound temperature rises to 120℃, add 4 parts of silane coupling agent Si69, and continue mixing until the rubber compound temperature reaches 155℃, then discharge the rubber, sheet it, cool and let it stand for 18 hours to obtain the first stage masterbatch.
[0030] Two-stage mixing: The first-stage masterbatch is put into the internal mixer, and the rotor speed is controlled at 60 rpm. Then, 15 parts of carbon black N339 and 2.2 parts of antioxidant 4020 are added. The mixture is heated to 145°C and mixed for 3 minutes. The glue is then discharged and the sheet is cooled to 40°C to obtain the second-stage masterbatch.
[0031] Final mixing: The second stage masterbatch is put back into the internal mixer, and 1.7 parts of sulfur, 1.7 parts of accelerator CZ and 0.16 parts of anti-scorching agent CTP are added in sequence. The mixture is heated to 110°C and mixed for 5 minutes. After the components are mixed evenly, the mixture is passed through a two-roll mill 5 times, and then the sheet is cooled and allowed to stand for 26 hours to obtain a flexural rubber composition.
[0032] Example 2 4.5 parts of titanium dioxide powder (model CY-T200, purchased from Hangzhou Jiupeng New Materials Co., Ltd.) and 45 parts of 90wt% ethanol aqueous solution were mixed and poured into a three-necked flask. The mixture was ultrasonically dispersed for 40 min, heated to 72℃ in an oil bath, and the pH was adjusted to 5.6 by adding glacial acetic acid. 0.1 parts of γ-aminopropyltriethoxysilane were added, and the mixture was refluxed for 4 h. The mixture was then placed in a drying oven and dried at 105℃ for 1 h. The resulting powder was dispersed in 45 parts of anhydrous ethanol, heated to 96℃, and 0.14 parts of N,N'-dicyclohexylcarbodiimide and 0.15 parts of 3,5-di-tert-butyl-4-hydroxyphenylacetic acid were added. The reaction was continued for 3.5 h, filtered, and washed twice with anhydrous ethanol. The mixture was then heated to 93℃ and vacuum dried for 11 h to obtain modified titanium dioxide powder.
[0033] Eight parts of attapulgite clay (0.15~0.5μm in length and 0.05~0.15μm in diameter, purchased from Xuyi Taihe High-tech Technology Co., Ltd.) were added to 460 parts of deionized water and stirred at 1000 rpm for 25 min. 46 parts of silica were added and stirred for another 35 min. Glacial acetic acid was added to adjust the pH to 5.5 to obtain a composite solution. 1.2 parts of silane coupling agent Si69 were added to 20 parts of 70wt% ethanol aqueous solution, the pH was adjusted to 5.5 and stirred for 40 min. The solution was then poured into the composite solution and heated to 65℃ and stirred for 3 h. The resulting slurry was spray-dried with the inlet air temperature controlled at 160℃ and the outlet air temperature at 80℃. It was then vacuum-dried at 100℃ for 3 h. After cooling, it was passed through a 100-mesh sieve to obtain secondary particles.
[0034] First stage of mixing: Mix 11 parts of natural rubber NR and 89 parts of emulsion styrene-butadiene rubber ESBR, heat to 60℃, and stir at 50 rpm for 10 min for initial plasticization; then add 52 parts of secondary granules, 4.5 parts of modified titanium dioxide powder, 3.2 parts of zinc oxide, 2.1 parts of stearic acid, 1.6 parts of protective wax, 1 part of antioxidant RD, 8.5 parts of environmentally friendly aromatic oil TDAE, 3.2 parts of C9 petroleum resin and 0.9 parts of accelerator DPG in sequence, and continue mixing for 4 min; when the rubber compound temperature rises to 115℃, add 3.8 parts of silane coupling agent Si69, and continue mixing until the rubber compound temperature reaches 150℃, then discharge the rubber, sheet it, cool and let it stand for 17 h to obtain the first stage masterbatch.
[0035] Two-stage mixing: The first-stage masterbatch is put into the internal mixer, and the rotor speed is controlled at 40 rpm. Then, 14.5 parts of carbon black N339 and 2.1 parts of antioxidant 4020 are added. The mixture is heated to 140°C and mixed for another 2 minutes before being discharged. The sheet is then cooled to 35°C to obtain the second-stage masterbatch.
[0036] Final mixing: The second stage masterbatch is put back into the internal mixer, and 1.6 parts of sulfur, 1.6 parts of accelerator CZ and 0.15 parts of anti-scorching agent CTP are added in sequence. The mixture is heated to 100°C and mixed for 4 minutes. After the components are mixed evenly, the mixture is passed through a two-roll mill 4 times, and then the sheet is cooled and allowed to stand for 24 hours to obtain a flexural rubber composition.
[0037] Example 3 Four parts of titanium dioxide powder (model CY-T200, purchased from Hangzhou Jiupeng New Materials Co., Ltd.) and 40 parts of 90wt% ethanol aqueous solution were mixed and poured into a three-necked flask. The mixture was ultrasonically dispersed for 35 min, heated to 70℃ in an oil bath, and glacial acetic acid was added to adjust the pH to 5. 0.1 parts of γ-aminopropyltriethoxysilane were added, and the mixture was refluxed for 4 h. The mixture was then placed in a drying oven and dried at 100℃ for 1 h. The resulting powder was dispersed in 40 parts of anhydrous ethanol, heated to 95℃, and 0.12 parts of N,N'-dicyclohexylcarbodiimide and 0.15 parts of 3,5-di-tert-butyl-4-hydroxyphenylacetic acid were added. The reaction was continued for 3 h, filtered, and washed twice with anhydrous ethanol. The mixture was then heated to 90℃ and vacuum dried for 10 h to obtain modified titanium dioxide powder.
[0038] Six parts of attapulgite clay (0.15~0.5μm in length and 0.05~0.15μm in diameter, purchased from Xuyi Taihe High-tech Technology Co., Ltd.) were added to 400 parts of deionized water and stirred at 800 rpm for 20 min. 45 parts of silica were added and stirred for another 30 min. Glacial acetic acid was added to adjust the pH to 5 to obtain a composite solution. 0.8 parts of silane coupling agent Si69 were added to 15 parts of 70wt% ethanol aqueous solution, the pH was adjusted to 5 and stirred for 30 min. The solution was then poured into the composite solution and heated to 60℃ and stirred for 2 h. The resulting slurry was spray-dried with the inlet air temperature controlled at 150℃ and the outlet air temperature at 70℃. It was then vacuum-dried at 90℃ for 2 h. After cooling, it was passed through a 100-mesh sieve to obtain secondary particles.
[0039] First stage of mixing: Mix 10 parts of natural rubber NR and 88 parts of emulsion styrene-butadiene rubber ESBR, heat to 50°C, and stir at 50 rpm for 8 minutes for initial plasticization; add 50 parts of secondary granules, 4 parts of modified titanium dioxide powder, 3 parts of zinc oxide, 2 parts of stearic acid, 1.5 parts of protective wax, 1 part of antioxidant RD, 8 parts of environmentally friendly aromatic oil TDAE, 3 parts of C9 petroleum resin and 0.8 parts of accelerator DPG in sequence, and continue mixing for 3 minutes; when the rubber compound temperature rises to 110°C, add 3.8 parts of silane coupling agent Si69, and continue mixing until the rubber compound temperature reaches 145°C, then discharge the rubber, sheet it, cool and let it stand for 16 hours to obtain the first stage masterbatch.
[0040] Two-stage mixing: The first-stage masterbatch is put into the internal mixer and the rotor speed is controlled at 40 rpm. Then, 14 parts of carbon black N339 and 2 parts of antioxidant 4020 are added. The mixture is heated to 130°C and mixed for another 2 minutes before being discharged. The sheet is then cooled to 30°C to obtain the second-stage masterbatch.
[0041] Final mixing: The second stage masterbatch is put back into the internal mixer, and 1.6 parts of sulfur, 1.6 parts of accelerator CZ and 0.15 parts of anti-scorching agent CTP are added in sequence. The mixture is heated to 90°C and mixed for 3 minutes. After the components are mixed evenly, the mixture is passed through a two-roll mill 3 times, and then the sheet is cooled and allowed to stand for 24 hours to obtain a flexural rubber composition.
[0042] Example 4 4.8 parts of titanium dioxide powder (model CY-T200, purchased from Hangzhou Jiupeng New Materials Co., Ltd.) and 47 parts of 90wt% ethanol aqueous solution were mixed and poured into a three-necked flask. The mixture was ultrasonically dispersed for 40 min, heated to 73℃ in an oil bath, and the pH was adjusted to 5.5 by adding glacial acetic acid. 0.1 parts of γ-aminopropyltriethoxysilane were added, and the mixture was refluxed for 4.5 h. The mixture was then placed in a drying oven and dried at 95℃ for 2 h. The resulting powder was dispersed in 45 parts of anhydrous ethanol, heated to 97℃, and 0.13 parts of N,N'-dicyclohexylcarbodiimide and 0.15 parts of 3,5-di-tert-butyl-4-hydroxyphenylacetic acid were added. The reaction was continued for 4 h, filtered, and washed three times with anhydrous ethanol. The mixture was then heated to 95℃ and vacuum dried for 12 h to obtain modified titanium dioxide powder.
[0043] 7.5 parts of attapulgite clay (0.15~0.5μm in length and 0.05~0.15μm in diameter, purchased from Xuyi Taihe High-tech Technology Co., Ltd.) were added to 500 parts of deionized water and stirred at 1200 rpm for 30 min. 47 parts of silica were added and stirred for another 40 min. Glacial acetic acid was added to adjust the pH to 6 to obtain a composite solution. 1.2 parts of silane coupling agent Si69 were added to 22 parts of 70wt% ethanol aqueous solution, the pH was adjusted to 6 and stirred for 60 min. The solution was then poured into the composite solution and heated to 70℃ and stirred for 4 h. The resulting slurry was spray-dried with the inlet air temperature controlled at 180℃ and the outlet air temperature at 90℃. It was then vacuum-dried at 90℃ for 2 h. After cooling, it was passed through a 200-mesh sieve to obtain secondary particles.
[0044] First stage of mixing: Mix 11.5 parts of natural rubber NR and 88.5 parts of emulsion styrene-butadiene rubber ESBR, heat to 70℃, and stir at 70 rpm for 12 minutes for initial plasticization; then add 53 parts of secondary granules, 4.55 parts of modified titanium dioxide powder, 3.5 parts of zinc oxide, 2.2 parts of stearic acid, 1.8 parts of protective wax, 1.1 parts of antioxidant RD, 9 parts of environmentally friendly aromatic oil TDAE, 3.5 parts of C9 petroleum resin and 1 part of accelerator DPG in sequence, and continue mixing for 5 minutes; when the rubber compound temperature rises to 120℃, add 4 parts of silane coupling agent Si69, and continue mixing until the rubber compound temperature reaches 155℃, then discharge the rubber, sheet it, cool and let it stand for 18 hours to obtain the first stage masterbatch.
[0045] Two-stage mixing: The first-stage masterbatch is put into the internal mixer, and the rotor speed is controlled at 60 rpm. Then, 14.5 parts of carbon black N339 and 2.2 parts of antioxidant 4020 are added. The mixture is heated to 145°C and mixed for another 3 minutes before being discharged. The sheet is then cooled to 40°C to obtain the second-stage masterbatch.
[0046] Final mixing: The second stage masterbatch is put back into the internal mixer, and 1.6 parts of sulfur, 1.7 parts of accelerator CZ and 0.15 parts of anti-scorching agent CTP are added in sequence. The mixture is heated to 110°C and mixed for 5 minutes. After the components are mixed evenly, the mixture is passed through a two-roll mill 5 times, and then the sheet is cooled and allowed to stand for 26 hours to obtain a flexural rubber composition.
[0047] Example 5 4.6 parts of titanium dioxide powder (model CY-T200, purchased from Hangzhou Jiupeng New Materials Co., Ltd.) and 44 parts of 90wt% ethanol aqueous solution were mixed and poured into a three-necked flask. The mixture was ultrasonically dispersed for 40 min, heated to 72℃ in an oil bath, and glacial acetic acid was added to adjust the pH to 5.6. 0.11 parts of γ-aminopropyltriethoxysilane were added, and the mixture was refluxed for 4 h. The mixture was then placed in a drying oven and dried at 105℃ for 1 h. The resulting powder was dispersed in 48 parts of anhydrous ethanol, heated to 95℃, and 0.13 parts of N,N'-dicyclohexylcarbodiimide and 0.16 parts of 3,5-di-tert-butyl-4-hydroxyphenylacetic acid were added. The reaction was continued for 3.5 h, filtered, and washed twice with anhydrous ethanol. The mixture was then heated to 93℃ and vacuum dried for 11 h to obtain modified titanium dioxide powder.
[0048] Nine parts of attapulgite clay (0.15~0.5μm in length and 0.05~0.15μm in diameter, purchased from Xuyi Taihe High-tech Technology Co., Ltd.) were added to 470 parts of deionized water and stirred at 1000 rpm for 25 min. 49 parts of silica were added and stirred for another 35 min. Glacial acetic acid was added to adjust the pH to 5.5 to obtain a composite solution. 1.3 parts of silane coupling agent Si69 were added to 22 parts of 70wt% ethanol aqueous solution, the pH was adjusted to 5.5 and stirred for 40 min. The solution was then poured into the composite solution and heated to 65℃ and stirred for 3 h. The resulting slurry was spray-dried with the inlet air temperature controlled at 160℃ and the outlet air temperature at 80℃. It was then vacuum-dried at 90℃ for 2 h. After cooling, it was passed through a 200-mesh sieve to obtain secondary particles.
[0049] First stage of mixing: 12 parts of natural rubber NR and 88 parts of emulsion styrene-butadiene rubber ESBR are mixed and heated to 60°C. The mixture is stirred at 50 rpm for 10 minutes for initial plasticization. Then, 54 parts of secondary granules, 4.8 parts of modified titanium dioxide powder, 3.4 parts of zinc oxide, 2.2 parts of stearic acid, 1.7 parts of protective wax, 1.1 parts of antioxidant RD, 8.2 parts of environmentally friendly aromatic oil TDAE, 3.3 parts of C9 petroleum resin and 1 part of accelerator DPG are added sequentially, and mixing is continued for 4 minutes. When the temperature of the rubber compound rises to 115°C, 4 parts of silane coupling agent Si69 are added, and mixing is continued until the temperature of the rubber compound reaches 150°C. The rubber is then discharged, sheeted, cooled and allowed to stand for 17 hours to obtain the first stage masterbatch.
[0050] Two-stage mixing: The first-stage masterbatch is put into the internal mixer, and the rotor speed is controlled at 40 rpm. Then, 14.5 parts of carbon black N339 and 2.1 parts of antioxidant 4020 are added. The mixture is heated to 140°C and mixed for another 2 minutes before being discharged. The sheet is then cooled to 35°C to obtain the second-stage masterbatch.
[0051] Final mixing: The second stage masterbatch is put back into the internal mixer, and 1.7 parts of sulfur, 1.6 parts of accelerator CZ and 0.16 parts of anti-scorching agent CTP are added in sequence. The mixture is heated to 100°C and mixed for 4 minutes. After the components are mixed evenly, the mixture is passed through a two-roll mill 4 times, and then the sheet is cooled and allowed to stand for 24 hours to obtain a flexural rubber composition.
[0052] Example 6 4.2 parts of titanium dioxide powder (model CY-T200, purchased from Hangzhou Jiupeng New Materials Co., Ltd.) and 40 parts of 90wt% ethanol aqueous solution were mixed and poured into a three-necked flask. The mixture was ultrasonically dispersed for 35 min, heated to 70℃ in an oil bath, and the pH was adjusted to 5 by adding glacial acetic acid. 0.11 parts of γ-aminopropyltriethoxysilane were added, and the mixture was refluxed for 4 h. The mixture was then placed in a drying oven and dried at 100℃ for 1 h. The resulting powder was dispersed in 40 parts of anhydrous ethanol, heated to 95℃, and 0.13 parts of N,N'-dicyclohexylcarbodiimide and 0.15 parts of 3,5-di-tert-butyl-4-hydroxyphenylacetic acid were added. The reaction was continued for 3 h, filtered, and washed twice with anhydrous ethanol. The mixture was then heated to 90℃ and vacuum dried for 10 h to obtain modified titanium dioxide powder.
[0053] 8.5 parts of attapulgite clay (0.15~0.5μm in length and 0.05~0.15μm in diameter, purchased from Xuyi Taihe High-tech Technology Co., Ltd.) were added to 480 parts of deionized water and stirred at 800 rpm for 20 min. 47 parts of silica were added and stirred for another 30 min. Glacial acetic acid was added to adjust the pH to 5 to obtain a composite solution. 1.1 parts of silane coupling agent Si69 were added to 20 parts of 70wt% ethanol aqueous solution, the pH was adjusted to 5 and stirred for 30 min. The solution was then poured into the composite solution and heated to 60℃ and stirred for 2 h. The resulting slurry was spray-dried with the inlet air temperature controlled at 150℃ and the outlet air temperature at 70℃. It was then vacuum-dried at 90℃ for 2 h. After cooling, it was passed through a 100-mesh sieve to obtain secondary particles.
[0054] First stage of mixing: Mix 11 parts of natural rubber NR and 89 parts of emulsion styrene-butadiene rubber ESBR, heat to 50℃, and stir at 50 rpm for 8 minutes for initial plasticization; then add 53 parts of secondary granules, 4.4 parts of modified titanium dioxide powder, 3.2 parts of zinc oxide, 2.1 parts of stearic acid, 1.7 parts of protective wax, 1.05 parts of antioxidant RD, 8.7 parts of environmentally friendly aromatic oil TDAE, 3.3 parts of C9 petroleum resin and 0.8 parts of accelerator DPG in sequence, and continue mixing for 3 minutes; when the rubber compound temperature rises to 110℃, add 4 parts of silane coupling agent Si69, and continue mixing until the rubber compound temperature reaches 145℃, then discharge the rubber, sheet it, cool and let it stand for 16 hours to obtain the first stage masterbatch.
[0055] Two-stage mixing: The first-stage masterbatch is put into the internal mixer, and the rotor speed is controlled at 40 rpm. Then, 14.5 parts of carbon black N339 and 2.1 parts of antioxidant 4020 are added. The mixture is heated to 130°C and mixed for 2 minutes. The mixture is then discharged and the sheet is cooled to 30°C to obtain the second-stage masterbatch.
[0056] Final mixing: The second stage masterbatch is put back into the internal mixer, and 1.65 parts of sulfur, 1.7 parts of accelerator CZ and 0.16 parts of anti-scorching agent CTP are added in sequence. The mixture is heated to 90°C and mixed for 3 minutes. After the components are mixed evenly, it is passed through a two-roll mill 3 times, and the sheet is cooled and allowed to stand for 24 hours to obtain a flexural rubber composition.
[0057] The present invention also includes comparative examples and related experiments.
[0058] Comparative Example 1 The only difference from Example 1 is that no modified titanium dioxide powder was added; all other components and preparation steps were exactly the same, resulting in a flexurally resistant rubber composition.
[0059] Comparative Example 2 The only difference from Example 1 is that 3,5-di-tert-butyl-4-hydroxyphenylacetic acid was not added; all other components and preparation steps were exactly the same, resulting in a flexurally resistant rubber composition.
[0060] Comparative Example 3 The only difference from Example 1 is that γ-aminopropyltriethoxysilane was not added; all other components and preparation steps were exactly the same, resulting in a flexurally resistant rubber composition.
[0061] Comparative Example 4 The only difference from Example 1 is that the attapulgite clay and silica were not prepared into secondary particles, but were directly added to a primary masterbatch. The other components and preparation steps were completely the same, and a flexural rubber composition was obtained.
[0062] Comparative Example 5 The only difference from Example 1 is that the attapulgite clay was treated with silane coupling agent Si69 and spray-dried, and then added to a masterbatch in sequence with silica. The other components and preparation steps were completely the same to obtain a flexural rubber composition.
[0063] Comparative Example 6 The only difference from Example 1 is that the silica was treated with silane coupling agent Si69 and spray-dried, and then added to a section of masterbatch in sequence with attapulgite clay. The other components and preparation steps were completely the same, and a flexural rubber composition was obtained.
[0064] Performance testing: The basic properties of the flexural rubber compositions prepared in Examples 1-6 and Comparative Examples 1-6 were tested for tensile strength, elongation at break, and 300% tensile strength in accordance with the national standard GB / T528-2009; and for tear strength in accordance with the national standard GB / T 529-2008. The test results are shown in Table 1.
[0065] The flexural resistance of the flexural rubber compositions prepared in Examples 1-6 and Comparative Examples 1-6 was tested for crack grade L according to national standard GB / T 11206-2009; and the crack grade L was tested according to national standard GB / T 7762-2014. 老化 The test results are shown in Table 1.
[0066] Table 1
[0067] As shown in Table 1, the flexural resistant rubber compositions prepared in Examples 1-6 have high tensile strength, elongation at break, 300% tensile strength, and tear strength, and the flexural cracking grade L and the flexural cracking grade L after aging are also high. 老化 All are grade 0, indicating that the present invention, through the combined use of modified titanium dioxide powder and secondary particles, can effectively improve the mechanical properties and flexural resistance of the rubber composition. Figure 1 The infrared reflectance spectrum of the flexurally resistant rubber composition prepared in Example 1 of this invention was obtained by testing with a Fourier transform infrared spectrometer.
[0068] Compared to Example 1, Comparative Example 1 did not add modified titanium dioxide powder, and the resulting rubber composition had a flexural cracking grade L after aging. 老化 The significant increase indicates that the addition of modified titanium dioxide powder can improve the flexural and aging resistance of the rubber composition; compared with Example 1, Comparative Example 2 did not add 3,5-di-tert-butyl-4-hydroxyphenylacetic acid, and the flexural cracking grade L of the obtained rubber composition after aging was significantly higher. 老化 The increase indicates that 3,5-di-tert-butyl-4-hydroxyphenylacetic acid is beneficial in enhancing the anti-aging protective effect of modified titanium dioxide powder, thereby improving the flexural resistance of the rubber composition. Compared with Example 1, the mechanical properties of the rubber composition obtained in Comparative Example 3 without the addition of γ-aminopropyltriethoxysilane decreased significantly, indicating that γ-aminopropyltriethoxysilane can improve the compatibility and dispersibility between titanium dioxide powder and rubber matrix, thereby improving the mechanical properties of the rubber composition.
[0069] Compared to Example 1, in Comparative Example 4, the attapulgite clay and silica were not made into secondary particles, resulting in a significant decrease in the mechanical properties and flexural resistance of the rubber composition. This indicates that secondary particles are beneficial for improving filler dispersion and reducing local stress concentration. In Comparative Examples 5 and 6, only the silane coupling agent Si69 was used to treat the attapulgite clay or silica alone, resulting in a decrease in the mechanical properties and flexural resistance of the rubber composition. This indicates that individual treatment cannot form an effective bridging structure between the two fillers. Therefore, by bridging the attapulgite clay and silica with Si69 to form secondary particles, the synergistic reinforcement and crack blocking effects of the two fillers can be utilized, thereby improving the mechanical properties and flexural resistance of the rubber composition.
[0070] The above are preferred embodiments of the present invention. Those skilled in the art can make several improvements and modifications without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a flexurally resistant rubber composition for new energy vehicle tires, characterized in that, The preparation steps include the following: S1. Mix 10-12 parts of natural rubber NR and 88-90 parts of emulsion styrene-butadiene rubber ESBR for initial plasticizing, then add 50-56 parts of secondary granules, 4-5 parts of modified titanium dioxide powder, zinc oxide, stearic acid, protective wax, antioxidant RD, environmentally friendly aromatic oil TDAE, C9 petroleum resin and accelerator DPG for compounding; then add silane coupling agent Si69 and continue compounding, sheet and cool to obtain a first stage of masterbatch; S2. Mix the first stage masterbatch, carbon black N339 and antioxidant 4020, heat to 130~145℃ for secondary mixing, and then sheet and cool to obtain the second stage masterbatch. S3. Mix the second-stage masterbatch, sulfur, accelerator CZ and anti-scorching agent CTP, heat and finish the process, pass through a thin sheet, and cool to obtain a flexural rubber composition. The modified titanium dioxide powder was prepared by dispersing titanium dioxide powder in an aqueous ethanol solution, adjusting the pH of the system to acidic, adding γ-aminopropyltriethoxysilane, refluxing, drying, dispersing in anhydrous ethanol, adding N,N'-dicyclohexylcarbodiimide and 3,5-di-tert-butyl-4-hydroxyphenylacetic acid to continue the reaction, and then filtering, washing and drying. The secondary particles were obtained by spray drying after attapulgite clay and silica were bridged with silane coupling agent Si69.
2. The method for preparing a flexurally resistant rubber composition for new energy vehicle tires according to claim 1, characterized in that, The secondary particles are prepared by dispersing attapulgite clay in deionized water, adding silica and stirring, adjusting the pH to 5-6 to obtain a composite solution; adding silane coupling agent Si69 to an ethanol aqueous solution, adjusting the pH to 5-6 and stirring evenly, then pouring it into the composite solution, heating and stirring to react, and finally spray drying, cooling and sieving.
3. The method for preparing a flexurally resistant rubber composition for new energy vehicle tires according to claim 1, characterized in that, The modified titanium dioxide powder is prepared by mixing titanium dioxide powder and an aqueous ethanol solution, ultrasonically dispersing for 35-45 min, heating to 70-75℃, adjusting the pH to 5-6 with glacial acetic acid, adding γ-aminopropyltriethoxysilane, refluxing for 4-4.5 h, drying, dispersing in anhydrous ethanol, heating to 95-97℃, adding N,N'-dicyclohexylcarbodiimide and 3,5-di-tert-butyl-4-hydroxyphenylacetic acid, reacting for 3-4 h, filtering, washing 2-3 times with anhydrous ethanol, and vacuum drying at 90-95℃ for 10-12 h.
4. The method for preparing a flexurally resistant rubber composition for new energy vehicle tires according to claim 1, characterized in that, In step S1, natural rubber NR and latex styrene-butadiene rubber ESBR are mixed and heated to 50~70℃ for initial plasticizing for 8~12 minutes. Secondary granules, modified titanium dioxide powder, zinc oxide, stearic acid, protective wax, antioxidant RD, environmentally friendly aromatic oil TDAE, C9 petroleum resin and accelerator DPG are added and mixed for 3~5 minutes. When the temperature rises to 110~120℃, silane coupling agent Si69 is added and mixing continues. When the temperature rises to 145~155℃, the glue is discharged, and the sheet is cooled and allowed to stand for 16~18 hours to obtain a first stage of masterbatch.
5. The method for preparing a flexurally resistant rubber composition for new energy vehicle tires according to claim 4, characterized in that, In step S2, a first-stage masterbatch, carbon black N339, and antioxidant 4020 are heated to 130~145℃ and mixed for 2~3 minutes, then sheeted and cooled to 30~40℃ to obtain a second-stage masterbatch.
6. The method for preparing a flexurally resistant rubber composition for new energy vehicle tires according to claim 5, characterized in that, In step S3, the second-stage masterbatch, sulfur, accelerator CZ and anti-scorching agent CTP are heated to 90~110℃ and mixed for 3~5 minutes, passed through a thin sheet 3~5 times, and then cooled and allowed to stand for 24~26 hours to obtain a flexural rubber composition.
7. The method for preparing a flexurally resistant rubber composition for new energy vehicle tires according to claim 1, characterized in that, The rubber composition further comprises the following raw materials in parts by weight: 3-3.5 parts zinc oxide, 2-2.2 parts stearic acid, 1.5-1.8 parts protective wax, 1-1.1 parts antioxidant RD, 8-9 parts environmentally friendly aromatic oil TDAE, 3-3.5 parts C9 petroleum resin, 0.8-1 part accelerator DPG, 3.8-4 parts silane coupling agent Si69, 14-15 parts carbon black N339, 2-2.2 parts antioxidant 4020, 1.6-1.7 parts sulfur, 1.6-1.7 parts accelerator CZ, and 0.15-0.16 parts scorching inhibitor CTP.
8. The method for preparing a flexurally resistant rubber composition for new energy vehicle tires according to claim 7, characterized in that, The modified titanium dioxide powder comprises the following raw materials in parts by weight: 4-5 parts titanium dioxide powder, 40-50 parts 90wt% aqueous ethanol solution, 0.1-0.11 parts γ-aminopropyltriethoxysilane, 0.12-0.15 parts N,N'-dicyclohexylcarbodiimide and 0.15-0.16 parts 3,5-di-tert-butyl-4-hydroxyphenylacetic acid.
9. The method for preparing a flexurally resistant rubber composition for new energy vehicle tires according to claim 7, characterized in that, The secondary particles comprise the following raw materials in parts by weight: 6-10 parts attapulgite clay, 45-50 parts silica, 400-500 parts deionized water, 0.8-1.5 parts silane coupling agent Si69, and 15-25 parts 70wt% aqueous ethanol solution.
Citation Information
Patent Citations
Anti-aging non-discoloring sidewall rubber composition and preparation method thereof
CN113416353A